Localized chemotherapy approaches and advanced drug delivery strategies: a step forward in the treatment of peritoneal carcinomatosis from ovarian cancer - Breusa, Silvia; Zilio, Serena; Catania, Giuseppina; Bakrin, Naoual; Kryza, David; Lollo, Giovanna (Frontiers in Oncology, 2023)
Peritoneal carcinomatosis (PC) is a common outcome of epithelial ovarian carcinoma and is the leading cause of death for these patients. Tumor location, extent, peculiarities of the microenvironment, and the development of drug resistance are the main challenges that need to be addressed to improve therapeutic outcome. The development of new procedures such as HIPEC (Hyperthermic Intraperitoneal Chemotherapy) and PIPAC (Pressurized Intraperitoneal Aerosol Chemotherapy) has enabled locoregional delivery of chemotherapeutics, while the increasingly efficient design and development of advanced drug delivery micro and nanosystems are helping to promote tumor targeting and penetration and to reduce the side effects associated with systemic chemotherapy administration. The possibility of combining drug-loaded carriers with delivery via HIPEC and PIPAC represents a powerful tool to improve treatment efficacy, and this possibility has recently begun to be explored. This review will discuss the latest advances in the treatment of PC derived from ovarian cancer, with a focus on the potential of PIPAC and nanoparticles in terms of their application to develop new therapeutic strategies and future prospects.